Succinate Dehydrogenase Loss in Familial Paraganglioma: Biochemistry, Genetics, and Epigenetics - Yeng F. Her; L. James Maher (International Journal of Endocrinology)
It is counterintuitive that metabolic defects reducing ATP production can cause, rather than protect from, cancer. Yet this is precisely the case for familial paraganglioma, a form of neuroendocrine malignancy caused by loss of succinate dehydrogenase in the tricarboxylic acid cycle. Here we review biochemical, genetic, and epigenetic considerations in succinate dehydrogenase loss and present leading models and mysteries associated with this fascinating and important tumor.